Healthy and happy citizens: The opportunities and challenges of co-producing citizens' health and well-being in vulnerable neighborhoods - Carola van Eijk; Wilma van der Vlegel-Brouwer; Jet Bussemaker (Administrative Sciences, 2023)
This explorative study aims to contribute to the debate about citizen involvement in (complex) medical and social issues. Our research goals are: (1) to explore the main opportunities, threats and challenges to co-producing healthcare in vulnerable communities from the perspective of professionals, co-producers (i.e., citizens with a volunteering role) and service users (i.e., patients); (2) to distil lessons for public managers concerning the main issues involved in designing co-production initiatives. We studied co-production initiatives in the Dutch city, The Hague. These initiatives were part of a broader, unique movement named 'Healthy and Happy The Hague', which aims to change the way healthcare/social services are provided. Two intertwined research projects combine insights from interviews, focus group meetings and observations. The first project analyzed a variety of existing co-production initiatives in several neighborhoods; the second project involved longitudinal participatory action research on what stakeholders require to engage in co-production. The two research projects showed similarities and differences in the observed opportunities/treats/challenges. The study found that empowering citizens in their role as co-producers requires major changes in the professionals' outlook and supporting role in the communities. It illustrates the potential of synergizing insights from healthcare governance and public administration co-production literature to benefit co-production practice.
Keywords: 350; citizen participation; co-production; healthcare inequalities; positive health; social services; vulnerable neighborhoods